Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Materi Persamaan Kuadrat - Nuraini, Intan; Afifurrahman, Afifurrahman (Jurnal of Math Tadris, 2023)
This research aims to identify the types of errors made by students in solving questions on quadratic equations based on castolan theory. The subjects of this research were 14 class X students. The type of research used is descriptive qualitative. The instruments used are test sheets and documentation. Based on the results of this research, it shows that students make mistakes when solving quadratic equation problems. The types of errors made are conceptual errors and procedural errors. Students make the most conceptual mistakes, such as incorrectly doing factoring, incorrectly determining variables x and constants, incorrectly writing quadratic formulas, and incorrectly writing circumference formulas. This is due to students' lack of understanding of concepts in solving mathematics problems so that teachers have an important role in minimizing the errors that students often make.